2014
DOI: 10.1016/j.bpj.2014.04.054
|View full text |Cite
|
Sign up to set email alerts
|

N-Nervonoylsphingomyelin (C24:1) Prevents Lateral Heterogeneity in Cholesterol-Containing Membranes

Abstract: This study was conducted to explore how the nature of the acyl chains of sphingomyelin (SM) influence its lateral distribution in the ternary lipid mixture SM/cholesterol/1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), focusing on the importance of the hydrophobic part of the SM molecule for domain formation. Atomic force microscopy (AFM) measurements showed that the presence of a double bond in the 24:1 SM molecule in mixtures with cholesterol (CHO) or in pure bilayers led to a decrease in the molecular pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 47 publications
(51 reference statements)
5
37
0
7
Order By: Relevance
“…In agreement with Epand et al [54], we also previously showed that when an unsaturated sphingolipid, oleoyl-SM or nervonoyl-SM, is included in a lipid mixture, no lateral phase separation is detected in fluid membranes containing Cho and DOPC (dioleylphophatidylcholine) [33]. Taking into account all these results, we suggest that the increment of SM, specifically the SM 18:1, in preeclamptic-MVM is directly related with the increment of the lipid order and the destabilization of caveolae.…”
Section: Accepted Manuscriptsupporting
confidence: 74%
See 4 more Smart Citations
“…In agreement with Epand et al [54], we also previously showed that when an unsaturated sphingolipid, oleoyl-SM or nervonoyl-SM, is included in a lipid mixture, no lateral phase separation is detected in fluid membranes containing Cho and DOPC (dioleylphophatidylcholine) [33]. Taking into account all these results, we suggest that the increment of SM, specifically the SM 18:1, in preeclamptic-MVM is directly related with the increment of the lipid order and the destabilization of caveolae.…”
Section: Accepted Manuscriptsupporting
confidence: 74%
“…Thus, SM and Cho, are relevant in determining lipid conformational order and packing [31][32][33]. In this context, in a previous report we demonstrated that independently of the Cho content, SM/PC ratio determines the lipid order of the membrane; as the SM/PC ratio increase, the order of the membrane also increase [33]. In the present paper, membrane order was determined by EPR in normal and preeclamptic-MVM vesicles.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
See 3 more Smart Citations